The need for physical culture - McDowell, Rose Edith (My University, 1893)
Introduction: Because of the very evidence and importance of this subject comparatively few persons give the proper attention to, or realize its place in their lives. Thoughts of it are generally narrowed to the one fact that it is a system of motions given to aid the weak and sickly portions of humanity, and for those persons having an abundance of time for practice. Few realize even what these simple motions mean; and aside from these in the physical education of the body come all the forms of exercise, the regulations of dress, of dirt, of work, and of sleep, the proper attention to cleanliness, in short, physical culture extends to every point that in anyway influences our physical being.
Citation: McDowell, Rose Edith. The need for physical culture. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Humanity; Physical culture; Education; Theses; Manuscripts (documents)